Strategic Development of Ketambe Nature Tourism: Integrating Local Wisdom and Community-Based Sociocultural Values in Southeast Aceh - Ahmad, Bayhaqi; Hastuti, Hastuti (Baileo: Jurnal Sosial Humaniora, 2025)
This study aims to formulate an appropriate strategy for developing the Ketambe nature tourism area by integrating local wisdom and community-based sociocultural values in Southeast Aceh. Despite its significant ecotourism potential, Ketambe’s local wisdom has not been optimally utilized as a core attraction. Employing a descriptive method with a qualitative approach, data were collected through interviews, observations, and documentation. Data analysis follows Miles, Huberman, and Saldana’s interactive model, comprising data collection, condensation, display, and conclusion drawing. A SWOT analysis was applied to identify a strategic development path. Findings reveal that Ketambe’s tourism development is supported by adequate accessibility, infrastructure, and cultural attractions rooted in local wisdom. Key dimensions include local resources (scenery, biodiversity), local culture, indigenous knowledge (Leuser Mountain legends), local skills (guiding and handicrafts), and local social processes (community interactions with nature and tourists). The SWOT matrix indicates a strategic position in quadrant III (score -0.13; 0.59), suggesting the need to minimize weaknesses to seize opportunities. The novelty of this research lies in its integration of local wisdom dimensions with strategic tourism planning—a rarely explored approach in this region. The study recommends synergy between cultural preservation and improved tourism facilities to enhance attractiveness while maintaining sociocultural identity.